Effects of shading on growth and photosynthetic metabolism in Dipteryx alata Vogel seedlings under flooding - Linné, Jéssica Aline; Jesus, Maílson Vieria; de Lima, Vânia Tomazelli [UNESP]; Reis, Lucas Coutinho; Dresch, Daiane Mugnol; de Paula Quintão Scalon, Silvana; Santos, Cleberton Correia (Springer Nature, 2021)
Currently, environmental climate changes are constant and severe, causing physiological, biochemical and morphological changes in plants, which may induce adaptation and acclimatization to abiotic stresses. Greater knowledge about plant ecophysiology, such as the effects of light/shading and water condition may help the production and implantation of seedlings in projects for the recovery of degraded areas. Therefore, the aim of this study was to evaluate the photosynthetic metabolism, growth and quality of Dipteryx alata Vogel seedlings under three shading levels: 0%—full sun, 30% and 70% with two water regimes: the control—75% of the water retention capacity in the substrate—and the flooding of seedlings for 60 days and 100 days of post-flooding, which this last period was called recovery phase. We verified that flooding was harmful to gas exchange, potential quantum efficiency of photosystem II, plant height, expansion of the specific leaf area and quality of seedlings. However, the species recovered most of characteristics evaluated at 100 days of post-flooding with the end of stress showing the best results under 30% shading. The combination of metabolic adjustments of this species indicates resilience and plasticity then it expresses tolerance in conditions of seasonal flooding.
Keywords: Baru; Degraded areas; Gas exchange; Light; Water stress